Safety, tolerability and pharmacokinetics of AFN-1252 administered as immediate release tablets in healthy subjects - Hafkin, Barry; Kaplan, Nachum; Hunt, Thomas L (Future microbiology, 2015)
AFN-1252 is a novel inhibitor of FabI, an essential enzyme in spp. This study was undertaken to assess the safety, tolerability and pharmacokinetic properties of AFN-1252, following oral administration in an ascending dose trial. This was a double-blind, randomized, placebo-controlled, two-part study. In Part I, single doses (QD) of 100, 200, 300, or 400 mg AFN-1252 were administered. In Part II, subjects received 200, 400, 600, or 800 mg (total daily dose) where 100, 200 and 400-mg doses were given twice in one day. AFN-1252 was well-absorbed with Cmax at 3-4 h when given once per day and 2.5-9 h when dosed twice in a single dosing day. T½ ranged from 8 to 11 h. Total and peak exposures of AFN-1252 increased nonlinearly. Adverse events were primarily mild and resolved promptly. Oral doses of AFN-1252 were safe and well tolerated. AFN-1252 has the potential for once or twice-a-day dosing for treatment of staphylococcal infections.